Assessment of transfer of morphological characteristics of Anomalous Aortic Origin of a Coronary Artery from imaging to patient specific 3D Printed models: A feasibility study. (April 2021) - Parthasarathy, Jayanthi; Hatoum, Hoda; Flemister, Dorma C.; Krull, Carly M.; Walter, Benjamin A.; Zhang, Wei; Mery, Carlos M.; Molossi, Silvana; Jadhav, Siddharth; Dasi, Lakshmi Prasad; Krishnamurthy, Rajesh
Highlights: A process for deriving geometrically accurate patient-specific models from CT angiographic data is described for anomalous aortic origin of the coronary arteries, the most common detectable cause of sudden cardiac death in children. The described technique incorporates pathological elements derived from standard of care imaging to create realistic 3-D printed models that may be used for hemodynamic experiments to answer questions regarding clinical risk stratification and surgical decision making. 3DP models facilitate downstream hemodynamic flow evaluation and refinement of criteria for risk stratification, patient education, and therapeutic decision-making. Abstract: Background and Objective: This study aims to determine the accuracy of patient specific 3D printed models in capturing pathological anatomical characteristics derived from CT angiography (CTA) in children with anomalous aortic origin of a coronary artery (AAOCA). Methods & Materials: Following institutional regulatory approval, a standardized protocol for CTA of AAOCA was utilized for imaging. Blood volume of the aorta and coronaries were segmented from the DICOM images. A total of 10 models from 8 AAOCA patients were created, including 2 post-operative models. Mechanical properties of Agilus30 a flexible photopolymer coated with a thin layer of parylene, polyurethane (PU) and silicone and native aortic tissue from a postmortem specimen were compared. AAOCA models with wall thicknesses of 2mm aorta and 1.5mm coronaries were 3D printed in Agilus30 and coated with PU. CT of the printed models was performed, and 3D virtual models were generated. Transfer of anatomical characteristics and geometric accuracy were compared between the patient model virtual models. Results: Dynamic modulus of Agilus30 at 2mm thickness was found to be close to native aortic tissue. Structured reporting of anatomical characteristics by imaging experts showed good concordance between patient and model CTA Comparative patient and virtual model measurements showed Pearson's correlation (r) of 0.9959 for aorta (n=70) and 0.9538 for coronaries (n=60) linear, and 0.9949 for aorta (n=30) and 0.9538 for coronaries (n=30) cross-sectional, dimensions. Surface contour map mean difference was 0.08 ± 0.29mm. Conclusions: Geometrically accurate AAOCA models preserving morphological characteristics, essential for risk stratification and decision-making, can be 3D printed from a patient's CTA. Graphical abstract: Image, graphical abstract